Silybin Cocrystals with Improved Solubility and Bioavailability - Bingqing Zhu; Zhenfeng Ding; Xiaoyi Rong; Shengqiang Li; Xuefeng Mei (Pharmaceuticals)
Backgroud/Objectives: Silymarin, an extract from milk thistle, is widely recognized for its therapeutic potential in treating liver disorders. However, its clinical utility is limited by the poor solubility and low bioavailability of its key active ingredient, Silybin. In this study, we sought to address this issue through the development of a novel cocrystal of Silyin. Methods: Silybin-L-proline cocrystal was synthesized and the physicochemical properties of the cocrystal were characterized by PXRD, TGA, DSC, and FTIR. Dissolution tests were conducted in various pH solutions, and the impact of precipitation inhibitors was evaluated. Furthermore, pharmacokinetic study in rats were performed to assess the bioavailability. Results: The dissolution studies demonstrated that the cocrystal has a significant improvement in dissolution performance, particularly in acidic environments. Furthermore, the use of precipitation inhibitors, such as PVP, prolonged the supersaturation period for adequate absorption. Pharmacokinetic studies in rats revealed that the cocrystal exhibited a 16-fold increase in bioavailability compared to the raw Silybin extract, outperforming the commercial Silybin–phosphatidylcholine complex. Conclusions: The Silybin–L-proline cocrystal significantly enhances dissolution and bioavailability, indicating its potential to improve the therapeutic efficacy of Silybin in clinical applications.